In vitro activity of tigecycline in combination with various antimicrobials against multidrug resistant Acinetobacter baumannii - Petrosillo Nicola; Capone Alessandro; D'Arezzo Silvia; Principe Luigi; Visca Paolo (Annals of Clinical Microbiology and Antimicrobials, 2009)
Abstract Background Infections sustained by multidrug-resistant (MDR) and pan-resistant Acinetobacter baumannii have become a challenging problem in Intensive Care Units. Tigecycline provided new hope for the treatment of MDR A. baumannii infections, but isolates showing reduced susceptibility have emerged in many countries, further limiting the therapeutic options. Empirical combination therapy has become a common practice to treat patients infected with MDR A. baumannii, in spite of the limited microbiological and clinical evidence supporting its efficacy. Here, the in vitro interaction of tigecycline with seven commonly used anti-Acinetobacter drugs has been assessed. Methods Twenty-two MDR A. baumannii isolates from Intensive Care Unit (ICU) patients and two reference strains for the European clonal lineages I and II (including 3, 15 and 6 isolates that were resistant, intermediate and susceptible to tigecycline, respectively) were tested. Antimicrobial agents were: tigecycline, levofloxacin, piperacillin-tazobactam, amikacin, imipenem, rifampicin, ampicillin-sulbactam, and colistin. MICs were determined by the broth microdilution method. Antibiotic interactions were determined by chequerboard and time-kill assays. Only antibiotic combinations showing synergism or antagonism in both chequerboard and time-kill assays were accepted as authentic synergistic or antagonistic interactions, respectively. Results Considering all antimicrobials in combination with tigecycline, chequerboard analysis showed 5.9% synergy, 85.7% indifference, and 8.3% antagonism. Tigecycline showed synergism with levofloxacin (4 strains; 16.6%), amikacin (2 strains; 8.3%), imipenem (2 strains; 8.3%) and colistin (2 strains; 8.3%). Antagonism was observed for the tigecycline/piperacillin-tazobactam combination (8 strains; 33.3%). Synergism was detected only among tigecycline non-susceptible strains. Time-kill assays confirmed the synergistic interaction between tigecycline and levofloxacin, amikacin, imipenem and colistin for 5 of 7 selected isolates. No antagonism was confirmed by time-kill assays. Conclusion This study demonstrates the in vitro synergistic activity of tigecycline in combination with colistin, levofloxacin, amikacin and imipenem against five tigecycline non-susceptible A. baumannii strains, opening the way to a more rationale clinical assessment of novel combination therapies to combat infections caused by MDR and pan-resistant A. baumannii.